Dampak Keteladanan Yesus sebagai Guru Agung bagi Guru Pendidikan Agama Kristen Masa Kini - Ramses Simanjuntak (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
The teacher's role is very important in the education process. A teacher not only delivers course content tothe students, but also provides character education by being an example of good character and integrity. Therefore, the task of a teacher is a noble task. It is an honorable profession. In the context of Christian Education, Jesus Christ must become our main example and the Master ofthe education process, lead by a christian teacher. Jesus is the Teacher of all teachers, He not only delivers informations and knowedge, but also changes the life of the people who follow Him.